Hsa-miR-146b-3p promotes endothelial cell dysfunction and atherosclerosis development by targeting CREB3L3 to regulate the PI3K/Akt signaling pathway - Shifan ZHOU; Shuming ZHANG; Ningyuan CHEN; Ling HUANG; Chongyang SONG; Shangling PAN; Junhua PENG (Guangxi Yike Daxue xuebao)
Objective To explore the effects of hsa-miR-146b-3p on endothelial cells and the possible roles and mechanisms of hsa-miR-146b-3p in the development of atherosclerosis. Methods Lentivirus was used to construct an endothelial cell intervention model in EA. hy926 cells. The cells were categorized into two distinct groups: overexpression groups, including the OE_hsa-miR-146b-3p group and the OE_control group; and silencing groups, consisting of the SH_hsa-miR-146b-3p group and the SH_control group. The cell counting kit-8 (CCK-8) assay was used to detect the proliferation ability of cells, while scratching and Transwell assays were employed to assess the migration ability. Cell cycle and apoptosis assays were respectively conducted to explore the distribution characteristics and apoptosis rate of cells. The downstream targets of hsa-miR-146b-3p were verified by RNA sequencing (RNA-seq) and dual-luciferase assay. Finally, the expression levels of target genes were detected by reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and western blotting. Results Compared with the control group, overexpression of hsa-miR-146b-3p significantly promoted the proliferation (P < 0.01), migration (P < 0.0001) of EA.hy926 cells and the cell proportion in the S phase (P < 0.01), and increased the late apoptosis rate and total apoptosis rate (P < 0.05). The silencing groups showed inhibited proliferation (P < 0.05), weakened migration (P < 0.0001), a decreased proportion of cells in the S phase (P < 0.05), and reduced early-stage apoptosis (P < 0.05). RNA-seq combined with dual-luciferase assay confirmed that hsa-miR- 146b-3p regulated CREB3L3 via the PI3K/Akt pathway (P < 0.001). RT-qPCR and western blotting results showed that overexpression of hsa-miR-146b-3p led to a decrease in CREB3L3 expression level. Conclusion Hsa-miR-146b-3p may influence the function of endothelial cells and promote the development of atherosclerosis by downregulating the expression level of the CREB3L3 gene and the PI3K/Akt pathway.